Indonesia : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that sound macroeconomic management and exchange rate flexibility have bolstered policy credibility and external resiliency in Indonesia over the past 18 months. In the face of Federal Reserve tapering and headwinds posed by slumping commodity prices, policy and reserve buffers have been strengthened through a clearer policy framework and better policy coordination. Notwithstanding commodity sector developments and global risk factors, the near-term outlook is broadly positive. Looking ahead, the main challenge for Indonesia is to chart a course to higher, more inclusive growth, while preserving macrofinancial stability and further strengthening the external position.